1991
DOI: 10.1177/014107689108400809
|View full text |Cite
|
Sign up to set email alerts
|

Duodeno-gastric Reflux and Gastric Adenomas: A Scintigraphic Study in Patients with Familial Adenomatous Polyposis

Abstract: SummaryTo test whether the presence of gastric adenomas (dysplasia) was associated with gastric reflux of duodenal contents, six patients with familial adenomatous polyposis (FAP) who had gastric adenomas and nine matched FAP patients without gastric adenomas underwent scintigraphic duodeno-gastric reflux scanning. Reflux was graded 0-6, where O=no reflux, l=intermittent reflux into antrum only, 2=prolonged reflux into antrum only, 3=intermittent reflux into body, 4=prolonged reflux into body, 5=intermittent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Although pancreatico-duodenectomy (Whipple operation) would presumably be an effective preventive treatment, it is a major procedure with significant potential morbidity. Furthermore, following a Whipple procedure, bile would likely continue to have a deleterious effect on the jejunum at the choledojejunal anastomosis since bile may be a promoting factor for the development of adenomatous duodenal polyps [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Although pancreatico-duodenectomy (Whipple operation) would presumably be an effective preventive treatment, it is a major procedure with significant potential morbidity. Furthermore, following a Whipple procedure, bile would likely continue to have a deleterious effect on the jejunum at the choledojejunal anastomosis since bile may be a promoting factor for the development of adenomatous duodenal polyps [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of foregut adenomas in FAP mirrors mucosal exposure to bile, suggesting a role for bile in the pathogenesis of these lesions. Support for this hypothesis comes from studies that have shown an excess of DNA adducts -chemical modifications of DNA implicated in the initiation of carcinogenesis [54] in the duodenum of FAP patients [55,56], along with scintigraphic studies, which have demonstrated that adenoma distribution mirrors bile reflux in FAP [57].…”
Section: Pattern and Pathology Of Foregut Disease In Fapmentioning
confidence: 99%
“…Pancreatic endocrine insufficiency requiring exogenous insulin therapy is a complication in at least 3–6 per cent, whereas exocrine insufficiency is observed in 30–60 per cent of patients39. A pancreaticogastric anastomosis with preservation of the pylorus should be considered in FAP; preservation of the pylorus decreases biliary reflux into the stomach, which is thought to be a risk factor in the development of gastric polyps in patients with FAP40, 41. Any residual duodenum must be monitored for polyps40, 42.…”
Section: Resultsmentioning
confidence: 99%
“…A pancreaticogastric anastomosis with preservation of the pylorus should be considered in FAP; preservation of the pylorus decreases biliary reflux into the stomach, which is thought to be a risk factor in the development of gastric polyps in patients with FAP40, 41. Any residual duodenum must be monitored for polyps40, 42. An anatomically correct reconstruction is the goal, both to facilitate surveillance and to maximize the length of functioning small bowel in patients who may have undergone restorative proctocolectomy previously35.…”
Section: Resultsmentioning
confidence: 99%